Rola postaw rodzicielskich w kształtowaniu umiejętności życiowych dorosłych osób z niepełnosprawnością intelektualną - Maciejewska, Barbara; Janiszewska-Nieścioruk, Zdzisława (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the life of individuals with intellectual disability, a significant role is played by their family and their family`s attitudes towards them. This is because they are important for their development, education, rehabilitation, and social inclusion in all spheres of life activity. Negative or incorrect parental attitudes, e.g. parents distancing themselves from the child, not accepting or rejecting the child or being overprotective and limiting the child`s autonomy, may consequently result in a poorer development of life skills. Therefore, considering the role of parental attitudes, both positive and negative, in the empowerment and development of adaptive skills of adults with intellectual disabilities, a study was conducted to determine the relationship between the indicated variables. The results obtained, showed among other things, that the mother?s attitude of autonomy significantly correlates with the level of life skills of the occupational therapy participants included in the study.
Keywords: postawy rodzicielskie; umiejętności życiowe; dorosłe osoby z niepełnosprawnością intelektualną; parenting attitudes; life skills; adults with intellectual disability